ANALYZING THE SPATIAL DISTRIBUTION OF CRIME: A CASE STUDY OF BADABER VILLAGE PESHAWAR, PAKISTAN - Shehla Gul; Rafiq Ali Khan; Aitzaz Ahsan; Sartaj Aziz Khan; Shahid Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
This study provides a comprehensive spatial analysis of crime patterns in Badhaber, a village in KP, Pakistan, utilizing both primary and secondary data sources. The primary data comprises 1,064 First Information Reports (FIRs) collected from the Badhaber Police Station, detailing incidents of murder, narcotics offenses, and kidnapping over a specified period. Secondary data was gathered from police records, reports, journals, and online resources, further enriching the dataset. The methodology involved a systematic analysis of the collected data using various software tools, including MS Word, MS Excel, PowerPoint, and ArcGIS. This multi-step approach allowed for the detailed examination of crime patterns and the identification of crime hotspots within the village. The analysis revealed that specific zones, particularly the villages of Musa Zai, Bazid Khel, and Teh Bahader, exhibited higher concentrations of criminal activity, particularly in murder and narcotics-related crimes. The findings of this study have significant policy implications, emphasizing the need for targeted law enforcement, community-centric crime prevention strategies, and improved urban planning in high-risk areas. The study also highlights the importance of data-driven policy formulation and recommends the establishment of a dedicated crime analysis unit to continuously monitor and respond to crime trends. Future research directions include longitudinal studies, broader geographic analyses, and deeper investigations into the socioeconomic factors contributing to crime in the region.